AN INTEGRATIVE APPROACH TO TEACHING ENGLISH FOR YOUNG LEARNERS - Shamsiddin Raisov, Shamsiddin Raisov (Журнал иностранных языков и лингвистики, 2021)
The main function of integrationprocesses is to achieve a synergistic effect based oncooperation and collaboration that prevail over differentiation and isolation. Integration processes lead to the formation of new elements, changing, transforming the current ones into more effective. Scientists have confirmed the need to create fundamental pedagogical structures, the task of which will be the formation of a general culture of students, preparation for successful professional activity and the development of a holistic worldview. An integrative approach, formed in the domestic and foreign methodology, is presented in this communication is the most productive and effective. He can solve the problem holistic training of future specialists due not only to the integration of disciplines, but also to the fusion of methods, forms and organization of the educational process. consider the structure of an integrative approach to learning foreign language. It includes aspects, principles, goals and the result. Let's consider the components of the integrative approach: methodological, organizational and activity-based and content.